Cardiomyocyte proliferation in cardiac development and regeneration: a guide to methodologies and interpretations - Leone, Marina; Magadum, Ajit; Engel, Felix (American Journal of Physiology-Heart and Circulatory Physiology, 2015)
The newt and the zebrafish have the ability to regenerate many of their tissues and organs including the heart. Thus, a major goal in experimental medicine is to elucidate the molecular mechanisms underlying the regenerative capacity of these species. A wide variety of experiments have demonstrated that naturally occurring heart regeneration relies on cardiomyocyte proliferation. Thus, major efforts have been invested to induce proliferation of mammalian cardiomyocytes in order to improve cardiac function after injury or to protect the heart from further functional deterioration. In this review, we describe and analyze methods currently used to evaluate cardiomyocyte proliferation. In addition, we summarize the literature on naturally occurring heart regeneration. Our analysis highlights that newt and zebrafish heart regeneration relies on factors that are also utilized in cardiomyocyte proliferation during mammalian fetal development. Most of these factors have, however, failed to induce adult mammalian cardiomyocyte proliferation. Finally, our analysis of mammalian neonatal heart regeneration indicates experiments that could resolve conflicting results in the literature, such as binucleation assays and clonal analysis. Collectively, cardiac regeneration based on cardiomyocyte proliferation is a promising approach for improving adult human cardiac function after injury, but it is important to elucidate the mechanisms arresting mammalian cardiomyocyte proliferation after birth and to utilize better assays to determine formation of new muscle mass.
EVALuna2:25502